Infectious mononucleosis presenting as bilateral acute dacryocystitis. Issue 12 (December 1990) - Atkinson, P L; Ansons, A M; Patterson, A
Abstract : A case of infectious mononucleosis presenting as bilateral acute dacryocystitis in a 7-year-old girl is reported. Acute dacryocystitis is uncommon in this age group, and an underlying systemic illness should be suspected particularly when it is bilateral.